Amplified cold transduction in native nociceptors by M-channel inhibition - Vetter, Irina; Hein, Alexander; Sattler, Simon; Heßler, Sabine; Touska, Filip; Bressan, Elisangela; Parra, Andres; Hager, Ulrich; Leffler, Andreas; Boukalova, Stepana; Nissen, Matthias; Lewis, Richard J.; et al. (The Journal of Neuroscience, 2013)
Topically applied camphor elicits a sensation of cool, but nothing is known about how it affects cold temperature sensing. We found that camphor sensitizes a subpopulation of menthol-sensitive native cutaneous nociceptors in the mouse to cold, but desensitizes and partially blocks heterologously expressed TRPM8 (transient receptor potential cation channel subfamily M member 8). In contrast, camphor reduces potassium outward currents in cultured sensory neurons and, in cold nociceptors, the cold-sensitizing effects of camphor and menthol are additive. Using a membrane potential dye-based screening assay and heterologously expressed potassium channels, we found that the effects of camphor are mediated by inhibition of Kv7.2/3 channels subtypes that generate the M-current in neurons. In line with this finding, the specific M-current blocker XE991 reproduced the cold-sensitizing effect of camphor in nociceptors. However, the M-channel blocking effects of XE991 and camphor are not sufficient to initiate cold transduction but require a cold-activated inward current generated by TRPM8. The cold-sensitizing effects of XE991 and camphor are largest in high-threshold cold nociceptors. Low-threshold corneal cold thermoreceptors that express high levels of TRPM8 and lack potassium channels are not affected by camphor. We also found that menthol-like camphor-potently inhibits Kv7.2/3 channels. The apparent functional synergism arising from TRPM8 activation and M-current block can improve the effectiveness of topical coolants and cooling lotions, and may also enhance TRPM8-mediated analgesia. © 2013 the authors.
CRIS-Team Scopus Importer:2021-07-19

Ciguatoxins Evoke Potent CGRP Release by Activation of Voltage-Gated Sodium Channel Subtypes Na(V)1.9, Na(V)1.7 and Na(V)1.1 - Touska, Filip; Sattler, Simon; Malsch, Philipp; Lewis, Richard J.; Reeh, Peter; Zimmermann, Katharina (Marine Drugs, 2017)
Ciguatoxins (CTXs) are marine toxins that cause ciguatera fish poisoning, a debilitating disease dominated by sensory and neurological disturbances that include cold allodynia and various painful symptoms as well as long-lasting pruritus. Although CTXs are known as the most potent mammalian sodium channel activator toxins, the etiology of many of its neurosensory symptoms remains unresolved. We recently described that local application of 1 nM Pacific Ciguatoxin-1 (P-CTX-1) into the skin of human subjects induces a long-lasting, painful axon reflex flare and that CTXs are particularly effective in releasing calcitonin-gene related peptide (CGRP) from nerve terminals. In this study, we used mouse and rat skin preparations and enzyme-linked immunosorbent assays (ELISA) to study the molecular mechanism by which P-CTX-1 induces CGRP release. We show that P-CTX-1 induces CGRP release more effectively in mouse as compared to rat skin, exhibiting EC50 concentrations in the low nanomolar range. P-CTX-1-induced CGRP release from skin is dependent on extracellular calcium and sodium, but independent from the activation of various thermosensory transient receptor potential (TRP) ion channels. In contrast, lidocaine and tetrodotoxin (TTX) reduce CGRP release by 53-75%, with the remaining fraction involving L-type and T-type voltage-gated calcium channels (VGCC). Using transgenic mice, we revealed that the TTX-resistant voltage-gated sodium channel (VGSC) Na(V)1.9, but not Na(V)1.8 or Na(V)1.7 alone and the combined activation of the TTX-sensitive VGSC subtypes Na(V)1.7 and Na(V)1.1 carry the largest part of the P-CTX-1-caused CGRP release of 42% and 34%, respectively. Given the contribution of CGRP to nociceptive and itch sensing pathways, our findings contribute to a better understanding of sensory symptoms of acute and chronic ciguatera that may help in the identification of potential therapeutics.
EVALuna2:33337